A cancer vaccine with dendritic cells differentiated with GM-CSF and IFNα and pulsed with a squaric acid treated cell lysate improves T cell priming and tumor growth control in a mouse model - Ananda Mookerjee; Michele Graciotti; Lana E. Kandalaft (BioImpacts, 2018)
Introduction: Ovarian cancer is one of the most lethal gynecologic cancers. Relapses after remission are common, hence novel strategies are urgently needed. Our group has previously developed a vaccination approach based on dendritic cells pulsed with HOCl-oxidized tumor lysates. Here we investigate the improvement of this vaccine strategy using squaric acid treatment of cancer cells during tumor lysate preparation and by differentiating dendritic cells in the presence of GM-CSF and IFNα. Methods: Induction of cell death by squaric acid treatment was assessed with propidium iodide (PI) and Annexin V in ID8 tumor cells. High mobility group box 1 (HMGB1) immunogenic status was analyzed using a western blot-based method, as previously described. For immunological tests, ID8 cells expressing ovalbumin (ova-ID8) were treated with squaric acid before cell lysis. DCs prepared with the canonical GM-CSF and IL-4 differentiation cocktail or IFNα and GM-CSF were pulsed with tumor cell lysates and further matured in the presence of IFNγ and LPS (4-DCs and α-DCs respectively). DCs were then used in co-culture assays with ova-specific T cells and IFNγ and IL-4 secretion measured by ELISA. DC phenotypes were characterized by FACS. Finally, DCs were tested in an ovarian cancer mouse model measuring body weight and animal survival. Results: Squaric acid treatment of mouse ovarian cancer cells induced tumor cell death as well as preserve HMGB1, a crucial Damage-associated molecular pattern (DAMP) signal, in its active reduced form. Squaric acid treatment of ID8-ova cells increased IFNγ and decreased IL-4 production from ova-specific T cells in co-culture experiments, promoting a more immunogenic cytokine secretion pattern. DCs differentiated in the presence of IFNα induced a considerable decrease in IL-4 production compared to canonical 4-DCs, without affecting IFNγ release. DC phenotyping demonstrated a more mature and immunogenic phenotype for IFNα-differentiated DCs. Vaccination in tumor-bearing mice showed that IFNα-differentiated DCs pulsed with squaric acid-treated lysates were the most potent at delaying tumor growth, improving animal survival. Conclusion: We identified squaric acid as a novel immunogenic treatment of tumor cells for cancer vaccines particularly efficient in prolonging animal survival when used in combination with IFNα-differentiated DCs. These promising results support future efforts for the clinical translation of this approach.